Functional Extension in Python for Simulating Discrete Events in Queueing Networks - Lobato, Renata Spolon; Spolon, Roberta [UNESP]; Manacero, Aleardo; De Oliveira, Gustavo Kenj Kuroda; Cavenaghi, Marcos Antonio (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The concept of queueing is ubiquitous in everyday life, whether in supermarkets, banks or amusement parks. The objective of studying queueing networks is to optimize models, either those already implemented or to be implemented, by reducing waiting time and potential financial losses by companies. Discrete event simulation plays a fundamental role complementing the study of queueing models as it can model and simulate real-life scenarios. Therefore, this work proposes the development of a functional extension (library) in Python for discrete event simulations, capable of reproducing and performing performance studies of different models available in the literature, in different computational systems. To validate our proposed solution, we used the SMPL functional extension developed by M. H. MacDougall in C language. Analyzing and comparing the solutions results, we concluded that the developed functional extension in this work is capable of reproducing the same results as a well-established implementation, but using a modern, easy-to-learn, and versatile programming language.
Extensão Funcional em Python para Simulação de Eventos Discretos em Redes de Fila
Keywords: functional extension.; queueing networks; simulation